Seasonal cycle of near‐bottom transport and currents in the northern Gulf of California. Issue 12 (9th December 2016) - Navarro, R.; López, M.; Candela, J.
Abstract: Seasonal cycles of near‐bottom transport and temperature over the sills of the Northern Gulf of California, as well as surface geostrophic velocity anomalies, are presented. Transport at the sills, where overflows occur, is toward the head of the gulf all year round with maximum in October and minimum in June. Furthermore, transport is 180 ° out of phase with the surface geostrophic velocity across the northern gulf, consistent with the exchange being strongest in October. Seasonal cycles of near‐bottom temperature and transport are also 180 ° out of phase, indicating that maximum water inflow is associated with the coolest water entering from the Pacific Ocean. Near‐bottom temperature over the northern Ballenas Channel sill has a maximum in early August, which is more in phase with the surface temperature and consistent with intense mixing in the channel. Geostrophic velocity at the northern gulf is in phase with that near the mouth of the gulf, and approximately in phase with the seasonal heat input through the mouth, calculated previously by Beron‐Vera and Ripa (2000). Moreover, the maximum lower‐layer, horizontal heat output of the Ballenas Channel occurs in November, approximately one month after the maximum transport through the San Lorenzo and Delfín sills. Therefore, heat loss results from the continuous near‐bottom inflow of relatively cold water at both sills which bound the deepest basins of the northern gulf. Moreover, the mean and seasonal cycles of heat and mass fluxes in the deepest basins of the northern gulf are almost everywhere in opposite directions. Key Points: Seasonal exchange of mass in the northern gulf is minimum in June and maximum in October with near‐bottom inflow and near‐surface outflow Maximum inflow of near‐bottom transport is associated to the coldest water entering the northern gulf from the Pacific Ocean Heat loss from the deep layer of Ballenas Channel is due to the inflow of relatively cold water through the overflows at the sills